DIGITAL ACCOUNTING: DIGITALIZATION OF TAX AND INSURANCE ACTIVITIES - Abdusalomova Istoraxon Ilhom qizi (Modern American Journals, 2025)
This article analyzes the digitalization of accounting, tax and insurance systems based on digital technologies, their effectiveness, advantages and problems. The impact of the digitalization process on enterprises and the state budget, as well as real examples based on digital reforms being implemented in Uzbekistan, are presented.
Keywords: Digital accounting, electronic tax, online insurance, digitalization, financial reporting, electronic systems.